Severe angioedema induced by tomato soup with alprazolam and muscle relaxant drug: A rare and complex drug-food interaction - Deep Inder,; Seema Manak,; Pawan Kumar, (Indian Journal of Case Reports, 2021)
Molecular interactions at the level of drug and food may lead to the reduced or enhanced effect of a concomitantly given drug or food nutrient. The resultant effects of such interactions may sometimes be severe to life-threatening. Here, we present a rare case of a 40-year-old male patient who developed severe angioedema secondary to drug-food interaction. The patient presented in emergency with complaints of angioedema face, rashes, and difficulty in breathing. History revealed that the patient had been prescribed analgesic muscle relaxant Flexon MR (t.i.d) for severe backache 1 day before. On day 2, the patient self-medicated with tablet alprazolam for inducing sleep followed by intake of hot concentrated tomato soup (350 ml). Within ½ h, the patient took Flexon MR. Following Flexon MR, the patient went drowsy and developed angioedema face and rashes on the whole body with difficulty in breathing. The patient was given injection adrenaline (i.m) injection followed by an injection of chlorpheniramine (i/m) stat. After stabilization of vitals, the patient was discharged.